RANCANG BANGUN SISTEM INFORMASI APOTEK BERBASIS WEB - Vilona Fitri Alfionita; Rika Harman (LPPM Universitas Putera Batam, 2024)
The research is dedicated to developing a web-based pharmacy information system tailored for Rafa Farma Pharmacy in Batam City, addressing limitations present in the current Acosys system. Acknowledging the pivotal role of pharmacies in public health, the proposed system strives to improve accessibility, efficiency, and information security. Utilizing web technology, it enables seamless access from various locations and devices, streamlining pharmacy operations.The system's design integrates features like recording drug transactions, precise stock monitoring, and an intuitive user interface. Its primary objective is to offer an efficient solution for pharmacy management, ultimately enhancing customer service. Rafa Farma Pharmacy serves as the main case study, with the objective of overcoming access restrictions associated with the current system. The envisioned web-based system, implemented using the PHP programming language, MySQL is utilized as the database for the system and employing the waterfall method, aligns with the broader trend of information systems enhancing operational efficiency, particularly in health and pharmacy services, thus contributing to overall public health improvement.